(untitled) (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze the influence of humble leadership and This study aims to analyze the influence of resale value and brand awareness on purchasing decisions of Toyota products in the city of Tasikmalaya. The research employs a quantitative approach using multiple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents who are Toyota users in the region. The findings indicate that both resale value and brand awareness simultaneously have a significant effect on purchasing decisions. Partially, each independent variable also has a positive and significant influence. These results highlight that consumers’ perception of resale value and their level of brand awareness play a crucial role in the decision-making process when purchasing Toyota vehicles. This study is expected to serve as a valuable reference for companies in formulating more effective and consumer-oriented marketing strategies.